Production and Structural Characterization of Lactobacillus helveticus Derived Biosurfactant. (19th November 2014) - Sharma, Deepansh; Saharan, Baljeet Singh; Chauhan, Nikhil; Bansal, Anshul; Procha, Suresh
Abstract : A probiotic strain of lactobacilli was isolated from traditional soft Churpi cheese of Yak milk and found positive for biosurfactant production. Lactobacilli reduced the surface tension of phosphate buffer saline (PBS) from 72.0 to 39.5 mNm −1 pH 7.2 and its critical micelle concentration (CMC) was found to be 2.5 mg mL −1 . Low cost production of Lactobacilli derived biosurfactant was carried out at lab scale fermenter which yields 0.8 mg mL −1 biosurfactant. The biosurfactant was found least phytotoxic and cytotoxic as compared to the rhamnolipid and sodium dodecyl sulphate (SDS) at different concentration. Structural attributes of biosurfactant were determined by FTIR, NMR ( 1 H and 13 C), UPLC-MS, and fatty acid analysis by GCMS which confirmed the presence of glycolipid type of biosurfactant closely similar to xylolipids. Biosurfactant is mainly constituted by lipid and sugar fractions. The present study outcomes provide valuable information on structural characterization of the biosurfactant produced by L. helveticus MRTL91. These findings are encouraging for the application of Lactobacilli derived biosurfactant as nontoxic surface active agents in the emerging field of biomedical applications.